THE ROLE OF LEADERSHIP STYLES IN ENHANCING WORKPLACE EFFECTIVENESS: CASE STUDY OF NIGERIAN MANUFACTURING FIRMS - Odunayo, Henry Adewale; Abe, Israel Olajide (Universitas Muhammadiyah Jakarta, 2024)
Nigeria’s diverse manufacturing sector, characterized by varying organizational structures, product portfolios, workforce demographics, and market scope, necessitates nuanced leadership strategies. This study delves into the multifaceted environment of Nigerian manufacturing, emphasizing the importance of adaptive leadership practices amid dynamic industrial demands. This study aims to assess the prevalent leadership styles in Nigerian manufacturing firms, evaluate the impact of leadership styles on workplace effectiveness, and recommend context-specific leadership strategies. A mixed-method approach was employed by combining quantitative and qualitative methods. A structured questionnaire was administered to 320 participants using stratified random sampling. Statistical analyses included chi-square tests and ANOVA. Thematic analysis was applied to the qualitative responses. The results show that there are significant differences in the prevalence of leadership styles, affirming the need for diverse approaches, which significantly impact workplace effectiveness across various dimensions, emphasizing their critical role. Context-specific leadership strategies were identified through thematic analysis, highlighting the importance of tailored approaches. This study reveals the dynamic landscape of leadership styles in Nigerian manufacturing. These findings underscore the necessity of adaptive leadership to optimize workplace effectiveness. Practical recommendations offer valuable insights for leaders and policymakers and promote organizational success in this sector.